Efficacy of oral testosterone undecanoate in children with androgen insensitivity syndrome - Liu, Y (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2024)
Objective: To investigate the efficacy and safety of oral testosterone therapy in individuals diagnosed with androgen insensitivity syndrome (AIS). Methods: A self-controlled study design was utilized, focusing on individuals with AIS who were genetically diagnosed at the Department of Endocrinology, Genetics, and Metabolism of Beijing Children's Hospital between 2009 and 2021. These patients underwent treatment involving the administration of testosterone. The primary observed indexes include the measurement of penis length, which should meet the minimal surgical standard (penis length≥2.5 cm) or greater than or equal to -2.5 s (lower limit of normal). Secondary observed indexes include penile length standard deviation score (PL-SDS), an increase in penis longitude (ΔPL), medication dosage, the course of therapy, and safety indicators, among others. There were 4 courses of treatment. After each course, patients were evaluated to determine whether termination of treatment was appropriate. Patients who exhibited inadequate post-treatment penile length growth were advised to continue with further treatment. The statistical methodology included t-test, and a Wilcoxon rank sum test to describe efficacy and safety. The patients were followed up until 2023. Results: The study comprised a total of 51 individuals with AIS, comprising 33 males and 18 females (gender of registered permanent residence). Among these patients, 10 were diagnosed with complete androgen insensitivity syndrome (CAIS) and 41 were diagnosed with partial androgen insensitive syndrome (PAIS). There were 2 children with CAIS were diagnosed by doctors and prescribed testosterone undecanoate, but the children did not really take medicine.The penile length of CAIS patients could not be measured (penile length<0.5 cm) before and after treatment. For PAIS patients, baseline penile length and PL-SDS were (2.3±0.6) cm and -3.7±1.3, respectively. The measurements for penile length and PL-SDS after each treatment course were recorded as follows: (2.7±0.8), (2.8±0.6), (2.6±0.4), (2.6±0.4) cm and -2.8±1.6, 2.5±1.6, 2.9±1.2, -3.2±0.9, respectively. Both penile length and PL-SDS interventions showed statistically significant gains when compared to the baseline performance of the 4 courses (t=4.05、3.56、2.55、2.23 and 3.88、3.50、2.50、2.19, all P<0.05). Before treatment, 13 PAIS patients (32%) reached 2.5 cm and seven (17%) reached greater than or equal to -2.5 s. Following the initial, subsequent, third, and fourth therapeutic interventions, 18 cases (44%), 24 cases (59%), 25 cases (61%), and 26 cases (63%) reached 2.5 cm, respectively. Additionally, A total of 12 cases (29%), 15 cases (37%), 20 cases (49%), and 21 cases (51%), respectively, were found to reach greater than or equal to -2.5 s. The study involved the longitudinal monitoring of patients with the highest recorded age being 13.7 years. The weight, height, body mass index, bone age/age, cholesterol, hemoglobin and so on were all within the normal range and the difference were not statistically significant (all P>0.05). All 49 patients were no abnormalities in blood electrolyte, liver and kidney function and thyroid function and no changes in precocious puberty, pubic hair growth, aggressive behavior, vulvar skin darkening, diarrhea or other conditions. Conclusions: Testosterone undecanote in children with CAIS was no effective. The initial course of treatment for patients with PAIS demonstrates observable enhancements in penile length and PL-SDS. For patients with inadequate penile length growth, continued treatment in subsequent courses (such as the second, third, and fourth courses) is recommended toenhance outcomes gradually. Testosterone undecanoate was safe and effective for the majority of individuals with PAIS patients, with few adverse effects and good treatment tolerance